What the new data protection regulation means for veterinary practices. Issue 2 (1st March 2018) - Read, Claire
Abstract : On 25 May 2018, the General Data Protection Regulation (GDPR) will come into force, bringing with it new obligations for any organisation that handles personal data – including veterinary practices. Here, Claire Read examines the new law, and considers the preparations necessary to make practices compliant.